Strong nebular He II emission induced by He+ ionizing photons escaping through the clumpy winds of massive stars - Roy, Arpita; Krumholz, M. R.; Salvadori, S.; Meynet, G.; Ekström, S.; Vink, J. S.; Sander, Andreas A. C.; Sutherland, R. S.; Paul, S.; Pallottini, A.; Skúladóttir, Á (Astronomy and astrophysics, 2025)
Context. The origin of nebular He II emission in both local and high-redshift galaxies remains an unsolved problem. Various theories have been proposed to explain it, including He II-ionizing photons produced by high mass X-ray binaries, ultra-luminous X-ray sources, or “stripped” He stars produced by binary interaction or evolution of rapidly rotating (v/vcrit ≫ 0.4) single massive stars, shock ionization, and hidden active galactic nuclei. All of these theories have shortcomings, however, leaving the cause of nebular He II emission unclear. Aims. We investigate the hypothesis that the photons responsible for driving nebular He II emission are produced by the evolution of single massive stars and/or Wolf-Rayet (WR) stars whose winds are on the verge of becoming optically thin due to clumping, thus allowing significant escape of hard ionizing photons. We combined models of stellar evolution with population synthesis and nebular models to identify the most favorable scenarios for producing nebular He II via this channel. Methods. We used the Modules for Experiments in Stellar Astrophysics (MESA) code to compute evolutionary tracks for stars with initial masses of 10 − 150 M⊙ and a range of initial metallicities and rotation rates. We then combined these tracks with a range of custom treatments of stellar atmospheres, which were intended to capture the effects of clumping, in the population synthesis code Stochastically Lighting Up Galaxies (SLUG) in order to produce the total ionizing photon budgets and spectra. We used these spectra as inputs to CLOUDY calculations of nebular emission at a range of nebular densities and metallicities. Results. We find that if WR winds are clumpy enough to become close to optically thin, stellar populations with a wide range of metallicities and rotation rates can produce He II ionizing photons at rates sufficient to explain the observed nebular I(He ii)/I(Hβ) ratio ∼0.004 − 0.07 found in He II-emitting galaxies. Metal-poor rapidly rotating stellar populations ([Fe/H] = −2.0, v/vcrit = 0.4) also reach these levels of He II production, even for partially clumpy winds. These scenarios also yield He ii, Hβ, and “blue bump” line equivalent widths comparable to those observed in He II emitters. Only for homogeneous non-clumpy winds did we fail to find combinations of metallicity and stellar rotation rate that yield I(He ii)/I(Hβ) values as high as those observed in He II emitters. Conclusions. Contrary to previous findings, we conclude that single WR stars can be a strong source for nebular He II emission if their winds are sufficiently clumpy. This scenario also reproduces a range of other properties found in He II emitters, suggesting that hard photons escaping through clumpy WR winds are a strong candidate to explain nebular He II-emission.